Population dynamics of sogata, Tagosodes orizicolus (Muir) (Hemiptera: Dephacidae), in irrigated rice ecosystem in Santa Catarina State, Brazil - Eduardo Rodrigues Hickel (Journal of the Selva Andina Biosphere)
The South American sogata, Tagosodes orizicolus (Muir) (Hemiptera: Delphacidae), population dynamics in irrigated rice ecosystem in Santa Catarina State, Brazil, is still unknown. This makes difficult the overall planning of integrated pest management measures to be implemented in farms. The aim of this study was monitoring the sogata incidence to know its population dynamics and its periods of greatest occurrence in rice fields. Weekly sweep net samplings were carried out in the following environments: rice field, fallow land and pasture. Each sample consisted of 30 pendulum strokes of the net, taken at five points in each environment. Concomitantly, light traps were set in irrigated rice fields at Epagri Experimental Station, in Itajaí, SC. From September 2020 to March 2024 the light traps were turned on, from 4pm to 9am once a week, except from April to August of each year when they remained turned off. The population dynamics of T. orizicolus in irrigated rice fields was characterized by a low number of individuals between October and December and a subsequent continuous increase of individual’s number from January onwards. In the off-season, the sogata population remains in areas with rice regrowth. In Itajaí, Santa Catarina, the largest populations in irrigated rice fields occurred in March.